INSPIRING ENTERPRISE RESOURCE PLANNING TO INFORMATION TECHNOLOGY NETWORKING SPRINGS IN APPREHENSION OF HUMAN RESOURCE - Dr.D.Arivazhagan, Dr.J.Rengamani, Dr.S.Poongavanam (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Most of the manufacturing companies are using Enterprise Resource Planning (ERP) to maintain the routine work like procuring raw material, keeping stock intact with the production, waste material management and warehouse maintenance etc. It is a strange that service-oriented organization are not using this software to maintain their service and goods. The concept of this paper is to identify the needs of people working in the networking service organizations and suggest solutions to them using ERP. This paper suggests the model of ERP in new dimension to meet the needs and improve their performance.